Study Von Savigny's Thinking About Morals in Law: Understanding Moral in the Concept of Law “Barenti Lako Syara’ Tradition, Syara Barenti Lako Kitabullah” - Dianto Dianto (Law Doctoral Program Universitas Muhammadiyah Surakarta, 2020)
Objective: This article aims to discuss moral boundaries in the Law According to Von Savigny and moral limits in the Law According to the Legal Concept Principles of “Barenti Lako Syara’ Tradition, syara barenti ko kitabullah”Methodology: The methodology used in this study is normative juridical research. This study uses a philosophical approach by exploring the philosophical basis of Law by linking legal science with the concept of customary Law.Findings: Von Savigny does not limit the moral meaning in Law whether good or bad, wrong or right, depends on morals in the habits of society that are not separate from morals and facts. Meanwhile, tau samawa based on the legal concept of “barenti lako syara’ tradition, sara barenti lako Kitabullah” means moral boundaries in Law, morals can be accepted into Law after the validation process with the book.Application of the Study: Customary Law has an indicator of moral constraints, so that applicable Law in general can also have indicators of moral limitations as customary Law.Originality/Novelty: Syara’ becomes a verification tool for morals in the customary Law of tau samawa and the book of Allah becomes a moral detector in the syara’ Keywords: Moral, Law, tradition, syara’